PERANCANGAN TATA LETAK FASILITAS LABORATORIUM PERAWATAN PESAWAT TERBANG - Poerwanto, Eko (Sekolah Tinggi Teknologi Adisutjipto, 2013)
Each system installed in the aircraft requires high accuracy . Aircraft maintenance will be able to be reliable if all maintenance support needs ergonomically designed . One factor that is needed in the laboratory is an ergonomic layout needs good facilities . The layout of the facility that will support in improving the accuracy required in aircraft maintenance . The purpose of this study is to determine and organize work area and all the optimal aircraft maintenance facilities . The method used is to use the ARC and the Work Sheet . Based on the results of the analysis using ARC and Work Sheet layout arrangement forms an ideal material for aircraft maintenance is fixed (fixed material location ) . While the treatment facility will be located around the main products,namely plane that is on the floor is desired perawatan. Hope STTA as sound institutions may have facilities aerospace aircraft maintenance practices are sufficient.